Kontestasi Aktor di TikTok Dalam Mencapai Popularitas - Etin Prihatina; Yuanita Apriliandini Siregar; Rakhmat Hidayat; Afdhal Afdhal (The Journal of Society and Media, 2022)
Akbari, Deni Adha, Bella Jastacia, Edi Setiawan, and Dwi Widya Ningsih. 2022. “The Marketing Power of TikTok: A Content Analysis in Higher Education.” Binus Business Review 13(2):159–70. Biały, Beata. 2017. “Social Media—From Social Exchange to Battlefield.” The Cyber Defense Review 2(2):69–90. Bourdieu, Pierre. 1984. Distinction A Social Critique of the Judgement of Taste. edited by R. Nice. Kittredge Hall: Harvard University Press. Bourdieu, Pierre. 1990. On Television. New York: The New Press. Bourdieu, Pierre. 1993. The Field of Cultural Production. New York: Columbia University Press. Bourdieu, Pierre, and Loic J. D. Wacquant. 1992. An Invitation to Reflexive Sociology. Cambridge: Polity Press. Burke, Ciaran Thomas, Nathan Emmerich, and Nicola Ingram. 2013. “Well-Founded Social Fictions: A Defence of the Concepts of Institutional and Familial Habitus.” British Journal of Sociology of Education 34(2):165–82. Driessens, Olivier. 2013. “Celebrity Capital: Redefining Celebrity Using Field Theory.” Theory and Society 42(5):543–60. Erel, Umut. 2010. “Migrating Cultural Capital: Bourdieu in Migration Studies.” Sociology 44(4):642–60. Go, Julian. 2013. “Decolonizing Bourdieu: Colonial and Postcolonial Theory in Pierre Bourdieu’s Early Work.” Sociological Theory 31(1):49–74. Grenfell, Michael, and David James. 2014. “Change in the Field: Changing the Field: Bourdieu and the Methodological Practice of Educational Research.” British Journal of Sociology of Education 25(4):507–23. Grenfell, Michael. 2008. Pierre Bourdieu: Key Concepts. Buckinghamshire: Acumen Publishing. Jeong, Taeseok, and Dong-Hoon Seol. 2022. “Theoretical Construction of a Fragmented Society.” Journal of Asian Sociology 51(1):97–128. Julien, Chris. 2015. “Bourdieu, Social Capital and Online Interaction.” Sociology 49(2):356–73. Kemp, Simon. 2021. “Digital 2021: The Latest Insights Into the ‘State of Digital.’” Https://Datareportal.Com 1–50. Khamis, Susie, Lawrence Ang, and Raymond Welling. 2017. “Self-Branding, ‘Micro-Celebrity’ and the Rise of Social Media Influencers.” Celebrity Studies 8(2):191–208. doi: 10.1080/19392397.2016.1218292. Kirby, Jeff. 2017. “Fleshing Out an Ecological Habitus.” Nature and Culture 12(2):89–114. Kisida, Brian, Jay P. Greene, and Daniel H. Bowen. 2014. “Creating Cultural Consumers: The Dynamics of Cultural Capital Acquisition.” Sociology of Education 87(4):281–95. Knox, Emily J. M. 2014. “Supporting Intellectual Freedom: Symbolic Capital and Practical Philosophy in Librarianship.” The Library Quarterly: Information, Community, Policy 84(1):8–21. doi: 10.1086/674033. Lizardo, Omar. 2014. “Taste and the Logic of Practice in Distinction.” Sociologický Časopis / Czech Sociological Review 50(3):335–64. Miller, Diana L. 2016. “Gender, Field, and Habitus: How Gendered Dispositions Reproduce Fields of Cultural Production.” Sociological Forum 31(2):330–53. Nitzky, William David. 2022. “Moving the Living and the Dead.” Asian Ethnology 81(1/2):173–206. Pertiwi, Femilia, and Irwansyah Irwansyah. 2020. “Personal Branding Ria Ricis Pada Media Sosial Instagram.” Jurnal Penelitian Komunikasi 23(1). doi: 10.20422/jpk.v23i1.631. Praswary, Delinda Shisma, and Gede Sri Darma. 2021. “Community Relations Millenial Content Creator in Forming A Brand Image.” International Journal of Economics, Business and Accounting Research (IJEBAR) 5(4). Riikonen, Ainikki. 2019. “Decide, Disrupt, Destroy.” Strategic Studies Quarterly 13(4):122–45. Roese, Vivian. 2018. “You Won’t Believe How Co-Dependent They Are.” Pp. 313–32 in From Media Hype to Twitter Storm, edited by P. Vasterman. Amsterdam University Press. Santoso, Edi. 2017. “Kontestasi Identitas Di Media Sosial (Diskursus Tentang Karakter Dan Bahasa Banyumas Di Weblog, Twitter Dan Facebook).” Prosiding Konferensi Nasional Komunikasi 01(01). Shullenberger, Geoff. 2020. “The New Net Delusion.” The New Atlantis (62):46–52. Stone, Lynda D., Charles Underwood, and Jacqueline Hotchkiss. 2012. “The Relational Habitus.” Human Development 55(2):65–91. Susilowati. 2018. “Pemanfaatan Aplikasi Tiktok Sebagai Personal Branding Di Instagram (Studi Deskriptif Kualitatif Pada Akun @bowo_allpennliebe).” Jurnal Komunikasi 9(2):176–85.   Wilterdink, Nico. 2017. “The Dynamics of Inequality and Habitus Formation. Elias, Bourdieu, and the Rise of Nationalist Populism.” Historical Social Research / Historische Sozialforschung 42(4 (162)):22–42. Xu, Jun, and Gillian Hampden-Thompson. 2012. “Cultural Reproduction, Cultural Mobility, Cultural Resources, or Trivial Effect? A Comparative Approach to Cultural Capital and Educational Performance.” Comparative Education Review 56(1):98–124. doi: 10.1086/661289. Yuliana, Dewi. 2022. “The Intensity of Use of Social Networking Applications on Self-Confidence.” Bisma The Journal of Counseling 6(1).